Knowledge Management Practices in Polícia Militar de Minas Gerais: a dialogue between tradition and contemporaneity in favor of organizational learning (Advances in Knowledge Representation, 2023)
This paper was written aimed to identify and analyze the Knowledge Management (KM) practices ongoing in the Polícia Militar de Minas Gerais (uniformized police agency of Minas Gerais State), addressing a comparison with the practices documented in KM specialized papers. Thus, where searched for publications in Brazil and abroad, where KM practices in public and private organizations were identified. After literature review, a bibliographic and document analysis of laws was done, approaching internal rules, electronic sites and other existing documents of the organization. The finds points that the organization already performs talent bank practices, GC holders as content spaces and tools of other practices related by the specialized literature.